The influence of sex on anthropometric methods and four scales for screening obstructive sleep apnea. Issue 4 (August 2022) - Sun, Xishi; Zheng, Zhenzhen; Chen, Riken; Huang, Huili; Lei, Wei; Peng, Min; Li, Xiongbin; Zhang, Nuofu; Cheng, Junfen
Abstract: Objectives: Obstructive Sleep Apnea (OSA) is a kind of respiratory disease that occurs apnea repeatedly during sleep. The purpose of this study was to investigate the influence of sex on anthropometric methods and four scales for screening OSA. Methods: The basic data and PSG data of 2108 patients who underwent PSG examination at the Sleep Medicine Center of the First Affiliated Hospital of Guangzhou Medical University from July 2017 to December 2020 were continuously included. Then the sensitivity, specificity, positive predictive value, negative predictive value, AUC and DOR of the anthropometric method and the four scales were calculated. Results: 2108 OSA patients were enrolled from the Sleep Medicine Center, including 1644 males (78.0%). The average neck circumference and waist circumference of male and female patients were respectively (39.4±3.4) cm and (96.7±13.8) cm, (34.6±3.5) cm and (90.1±11.6) cm. In female patients. the AUC of NoSAS was the largest. When AHI was 5, 15, and 30 evens/h as the cut-off point, in male patients, the sensitivity of NHR was the highest, in female patients, the sensitivity of WHR was the highest. Conclusions: NHR and WHR are good tools for screening OSA in male and female patients respectively. They are worthy of promotion.